K-space analysis of complex large-scale meta-structures using the Inhomogeneous Wave Correlation method. (1st January 2020) - Tufano, G.; Errico, F.; Robin, O.; Droz, C.; Ichchou, M.; Pluymers, B.; Desmet, W.; Atalla, N.
Highlights: Wavenumber identification method applied to three large-scale meta-structures. Experimental test conducted under both diffuse acoustic field and shaker excitation. Effect of the industrially-oriented small-scale resonators on the dynamic response. Local dynamics and multi-modal behavior identification in the wavenumber domain. Abstract: An inverse wavenumber identification tool is used to characterize the vibration behavior of three structures and meta-structures with different complexity levels: a plane steel panel, a curved thick composite sandwich shell and a stiffened aluminum aircraft sidewall panel. Bare structures are first studied and then equipped with spatially distributed small-scale resonators, leading to meta-structures. For the two curved panels, tests are conducted under diffuse acoustic field and point mechanical excitations. For each studied case, the effect of the industrially-oriented small-scale resonators is highlighted using frequency and wavenumber analysis, showing general attenuation of the vibration level and even band gaps occurrence. The complex wavenumber identification allows also estimating the structural loss factor in the composite sandwich panel, while the multi-modal behavior is captured in the aluminum aircraft sidewall panel.